Hes1/Hes5 Gene Inhibits Differentiation via Down-Regulating Hash1 and Promotes Proliferation in Cervical Carcinoma Cells. Issue 7 (1st October 2010) - Liu, Jia; Lu, Wei-Guo; Ye, Feng; Cheng, Xiao-dong; Hong, Die; Hu, Ying; Chen, Huai-zeng; Xie, Xing
Abstract : Introduction: Hairy and enhancer of split 1 ( Hes1 ) and Hes5 are target genes for the mammalian Notch pathway, which are highly expressed in epithelia in the process of embryogenesis or in neural stem cells, inhibit cell differentiation via the Notch-Hes-Hash signaling, and promote the survival of stem cells. Either Hes1 or Hes5 overactivation is likely to affect cell differentiation, thereby resulting in carcinogenesis. Methods: We transfected the diced small interference RNA into SiHa cells and detected cell differentiation and proliferation by immunocytochemistry, Western blot, and methyl thiazolyl tetrazolium assay. Results: Knockdown of Hes1 and Hes5 would up-regulate the downstream gene Hash1, but not the upstream gene Notch1 in the Notch-Hes-Hash pathway. After Hes1 / Hes5 RNA interference, expression of differentiation-associated proteins (including Nanog, stage-specific embryonic antigen 4, and tumor rejection antigen-1-60) was reduced, and the cell differentiation was promoted; meanwhile, the cell proliferation was inhibited, which was verified by detecting proliferation-associated proteins (eg, Ki-67, proliferating cell nuclear antigen) and methyl thiazolyl tetrazolium assay. Conclusions: Our findings suggest that Hes1 / Hes5 gene would inhibit the cell differentiation via down-regulating Hash1 and promote the cell proliferation in cervical carcinoma cells; the cell differentiation and proliferation can be reversed simultaneously by Hes1 / Hes5 knockdown using RNA interference.